1996
DOI: 10.1172/jci119073
|View full text |Cite
|
Sign up to set email alerts
|

B cells from patients with systemic lupus erythematosus display abnormal antigen receptor-mediated early signal transduction events.

Abstract: To understand the molecular mechanisms that are responsible for the B cell overactivity that is observed in patients with SLE, we have conducted experiments in which the surface immunoglobulin (sIg)-mediated early cell signaling events were studied. The anti-sIgM-mediated free intracytoplasmic calcium (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
139
2
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(146 citation statements)
references
References 78 publications
3
139
2
2
Order By: Relevance
“…The inability to properly terminate activation may therefore result in inappropriate responses. In this regard, it has been shown in SLE that B cells have abnormal Ag receptor-mediated early signal transduction events [68]. The authors showed that following the Ag receptor ligation, Ca 21 responses and PTK phosphorylation were abnormally high compared with other autoimmune diseases and controls.…”
Section: B-cell Signallingmentioning
confidence: 98%
“…The inability to properly terminate activation may therefore result in inappropriate responses. In this regard, it has been shown in SLE that B cells have abnormal Ag receptor-mediated early signal transduction events [68]. The authors showed that following the Ag receptor ligation, Ca 21 responses and PTK phosphorylation were abnormally high compared with other autoimmune diseases and controls.…”
Section: B-cell Signallingmentioning
confidence: 98%
“…Altered expression of B cell receptor (BCR)-signaling molecules, such as CD19, CD22, CD45, Lyn, SHIP, and SHP-1, has been described in human autoimmune conditions (19)(20)(21)(22). It has also been reported that B lymphocytes from SLE patients exhibit abnormal intracellular calcium mobilization after BCR stimulation (23).…”
mentioning
confidence: 99%
“…There are indications that abnormal B cell signaling may contribute to autoimmune diseases in humans as well. In patients with lupus, stimulation of circulating B cells through their surface IgM (sIgM) produces significantly higher Ca 2ϩ fluxes as compared with similarly induced responses of B cells from patients with other systemic rheumatic diseases (40). The overall level of sIgM-initiated protein tyrosyl phosphorylation was also significantly enhanced in peripheral B lymphocytes, and correlated with the augmented BCR-mediated, free Ca 2ϩ responses.…”
Section: Bcr Signaling Alterations In Humansmentioning
confidence: 99%